Work schedule characteristics associated with sleep disturbance among healthcare professionals in Europe and South Korea: a report from two cross-sectional surveys - Ari Min; Hye Chong Hong (BMC Nursing, 2022)
Abstract Background Healthcare professionals worldwide are prone to sleep disturbance. Such sleep disturbance is associated with lower patient safety and quality of care. Therefore, this study aimed to identify the prevalence of sleep disturbance and determine the effect of work schedule characteristics on sleep disturbance among healthcare professionals in Europe and South Korea. Methods We used the sixth European Working Conditions Survey and the fifth Korean Working Conditions Survey for analyses. The study included 2285 healthcare professionals aged 18–65 years. Work schedule characteristics included shift work, night work, working hours per week, long work hours (i.e., more than 10 hours per shift), quick return to work, having to come to work on short notice, and changes in work schedules. A multiple logistic regression analysis was performed. Results The overall prevalence of sleep disturbance was 37.7%. The multivariate logistic regression model indicated that long work hours, quick return to, having to come to work on short notice, and changes in work schedules were significant factors associated with sleep disturbance among healthcare professionals. Conclusion The findings revealed that several work schedule-related factors were associated with sleep disturbances in healthcare professionals in Europe and Korea. Institutions and policymakers should implement strategies and policies to reduce the unpredictability of work schedules to ensure an adequate rest period between shifts and to reduce sleep disturbances.